Bahasa Gaul: Kreativitas Linguistik Kaum Muda - Budi Suyanto (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2006)
Abstract The topic this article is discussing relates with the existence of slang which is recently used by teenagers and celebrities in Indonesia. Three major problems appear when we discuss about slang: (1) the existence of slang as language varian in Indonesian language, (2) linguistic creativity by the teenagers, and (3) social tactors influencing the creative process.The linguistic creativity by the teenagers will be analyzed using linguistic and sociolinguistic approach. The linguistic approach is used to explain the linguistic features slang and the forms of language resulted from the linguistic creativity. The sociolinguistic approach is used to explain the social background supporting the linguistic creative process.Slang shows the features of informal indonesian variety which is compact and simple. Mother tongue and English give their great influence on the use of Indonesian slang. Teenagers perform the linguistic creativity is to give modern and metropolis image. Key words: slang, teenagers, celebrities, sociolinguistic, linguistic creative